Incidencia de los factores sociales en el consumo de sustancias psicoactivas en adolescentes de un barrio del municipio de Riohacha (2022)
The research entitled Incidence of social factors in the consumption of psychoactive substances in adolescents in a neighborhood of the municipality of Riohacha was carried out, which had as a general objective, to describe the social factors associated with the consumption of SPA, perceived by adolescents in a neighborhood. from the district of Riohacha La Guajira. It is decided to work with these variables because the scourge of the consumption of psychoactive substances in Colombia is an endless context due to the impact it generates in multiple environments of affected families that in one way or another have had stories that are linked to the problem.